Multimodel precipitation responses to removal of U.S. sulfur dioxide emissions. Issue 9 (12th May 2017) - Westervelt, D. M.; Conley, A. J.; Fiore, A. M.; Lamarque, J.‐F.; Shindell, D.; Previdi, M.; Faluvegi, G.; Correa, G.; Horowitz, L. W.
Abstract: Emissions of aerosols and their precursors are declining due to policies enacted to protect human health, yet we currently lack a full understanding of the magnitude, spatiotemporal pattern, statistical significance, and physical mechanisms of precipitation responses to aerosol reductions. We quantify the global and regional precipitation responses to U.S. SO2 emission reductions using three fully coupled chemistry‐climate models: Community Earth System Model version 1, Geophysical Fluid Dynamics Laboratory Coupled Model 3, and Goddard Institute for Space Studies ModelE2. We contrast 200 year (or longer) simulations in which anthropogenic U.S. sulfur dioxide (SO2 ) emissions are set to zero with present‐day control simulations to assess the aerosol, cloud, and precipitation response to U.S. SO2 reductions. In all three models, reductions in aerosol optical depth up to 70% and cloud droplet number column concentration up to 60% occur over the eastern U.S. and extend over the Atlantic Ocean. Precipitation responses occur both locally and remotely, with the models consistently showing an increase in most regions considered. We find a northward shift of the tropical rain belt location of up to 0.35° latitude especially near the Sahel, where the rainy season length and intensity are significantly enhanced in two of the three models. This enhancement is the result of greater warming in the Northern versus Southern Hemispheres, which acts to shift the Intertropical Convergence Zone northward, delivering additional wet season rainfall to the Sahel. Two of our three models thus imply a previously unconsidered benefit of continued U.S. SO2 reductions for Sahel precipitation. Key Points: Models show that U.S. SO2 reductions increase precipitation globally and regionally Decreasing U.S. sulfate shifts the ITCZ northward in two of three models Wet season Sahel precipitation may increase up to 10% from 2000 levels